Pemerkiraan Parameter Tumbukan Model Viskoelastik Tak Linier Berbentuk Bola dengan Menggunakan Metode Pelacak Parameter - Budi Rahardjo (agriTECH, 1994)
The parameter tracking method was used to estimate the parameters of non linear viscoelastic spherical model during impact. A set of impact data of free Falling indoor lacrose ball used to estimate the parameters of the model. The results indicated that the three parameters of the Impact can be determined by the method appropriately. The impact parameters of non linear viscoelastic spherical object can be estimated with a single set of impact data.